Organization and analysis of costs related to the participation of judo athletes in international competitions during the pandemic period. - Koteja, Piotr Michał; Gaweł, Sylwester; Małodobry, Zbigniew (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The COVID-19 pandemic, emerging a century after the Spanish flu, posed unprecedented challenges to global health and various sectors, including sports. This article examines the profound impact of the pandemic on the sport of judo, exploring the adaptations, protocols, and challenges faced by the International Judo Federation (IJF), athletes, and organizers. The study analyzes the dynamics of the virus, preventive measures, and the development of judo-specific protocols, highlighting the need for a collective global response. Unique challenges faced by judo athletes, coaches, and organizers are discussed, including changes in training processes, isolation measures, and the economic impact on the sports industry. The study presents a detailed overview of the IJF's COVID-19 protocol, encompassing vaccination requirements, testing procedures, and entry conditions for participants. The judo community's response to the pandemic is contextualized within the broader context of global sports, emphasizing the need for innovative solutions and collaborative efforts. The article concludes with a comprehensive analysis of the financial implications of the pandemic on judo competitions, revealing a substantial increase in costs due to health and safety protocols. The global economic impact on the sports industry is outlined, emphasizing the need for targeted assistance and the exploration of digital solutions.